Empirical Study of Women and Their Contribution on Beef Cattle Farming in Rural Area, Yogyakarta, Indonesia - Guntoro, Budi (Medwell Journals, 2013)
This research, were aimed to investigate the level of participation and to analyze the social factor related to the level of women participation in raising beef cattle in the cattle farmers group in Yogyakarta. The study focused on Pandan Mulyo group, Poncosari village, Srandakan, Bantul. This research was a case study which gathered all women (wives) of farmer groups as respondents. This research was done by interview and questionnaire methods. The data were tabulated and analyzed using Spearman’s rank correlation, Chi-square phi test to analyze the relationship between social factors and level of participation. The results showed that social factors had significant correlation are respondents age (r = 0.222; p<0.01), respondents education(r = -0.173; p<0.05), cattle raising experience (r= -0.173; p<0.05), number of their own beef (r = 0.308; p<0.05) and perception of farmers group (p<0.05) with level of participation. Chi-square analyze indicated that farmer’s attitude had significant relationship (p<0.05) with level of participation by strength of= 0.679.